2022
DOI: 10.1155/2022/7334080
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicine Use among Type 2 Diabetes Patients in KZN

Abstract: Background. Traditional medicine (TM) is widely used in both developing and developed countries to assist in the attempt to curtail the prevalence and increase in diabetes mellitus. Approximately 53% of South Africans use TM to prevent and treat their diseases. There is no conclusive evidence regarding the safety and effectiveness of TM versus prescribed medicine. The most common therapies used by diabetics in Africa include herbal treatments, nutritional products, spiritual healing, and relaxation techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Additionally, it is essential to highlight the coexistence of TM and CM utilization, as observed in eight of the included articles. 13 , 14 , 18 , 22 , 26 , 30 , 32 , 33 The results from these studies revealed a prevalence of concomitant use of TM and CM ranging from 35.4% to 88.4%. The majority of the studies (n=5) reported a high prevalence rate of >60%.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Additionally, it is essential to highlight the coexistence of TM and CM utilization, as observed in eight of the included articles. 13 , 14 , 18 , 22 , 26 , 30 , 32 , 33 The results from these studies revealed a prevalence of concomitant use of TM and CM ranging from 35.4% to 88.4%. The majority of the studies (n=5) reported a high prevalence rate of >60%.…”
Section: Resultsmentioning
confidence: 85%
“… 18 The prevalence of TM use was assessed across various time frames in the included studies. Specifically, four studies measured TM use since the diagnosis of diabetes, 22 , 23 , 30 , 33 while two studies focused on the previous year. 20 , 29 Another two studies examined TM use within the last 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Africa, there exists a wide variation in the prevalence of herbal medicine use in the management of type 2 diabetes. The prevalence ranges from 27% in South Africa [28], 58% in Sudan [15], 62% in Ethiopia [17], 67.5% in Nigeria [18] and 80.2% in Egypt [24].…”
Section: Introductionmentioning
confidence: 99%